What if Valve-in-Valve TAVR fails? Is surgical re-replacement still an option in high-risk patients? A case report. - De Donno, Luca; Galligani, Alan; Maestri, Francesco; Gripshi, Florida; Pattuzzi, Claudia; Scarpanti, Matteo; Gabor, Elena Adelina; Manca, Arianna; Nicolini, Francesco (Acta Biomedica Atenei Parmensis, 2022)
Redo surgical aortic valve replacement has been the gold standard for the treatment of degenerated bioprostheses; however it carries an inherent risk associated with a reoperative open heart surgery. Valve-in-Valve transcatheter aortic valve implantation (ViV-TAVI) has emerged as an alternative approach. Few articles in literature review transcatheter aortic valve replacement’s failure rates, complications (i.e., valve dislocation, paravalvular leaks) and their surgical management. The rate of reoperations after a percutaneous approach is expected to increase, with the currently rising number of transcatheter procedures worldwide even in patients with a longer life expectancy. Valve dislocation is a rare but serious complication that can severely impact on the outcome of patients. Paravalvular leaks and structural valve degeneration are the most common causes of surgical re-intervention. We present the case of a complex patient with previous surgical aortic valve and ascending aorta replacement who underwent a transfemoral valve-in-valve TAVI for bioprosthesis degeneration, complicated by valve dislocation requiring surgical reoperation.